2015
DOI: 10.1002/ijc.29649
|View full text |Cite
|
Sign up to set email alerts
|

The role of HPV RNA transcription, immune response‐related gene expression and disruptiveTP53mutations in diagnostic and prognostic profiling of head and neck cancer

Abstract: Stratification of head and neck squamous cell carcinomas (HNSCC) based on HPV16 DNA and RNA status, gene expression patterns, and mutated candidate genes may facilitate patient treatment decision. We characterize head and neck squamous cell carcinomas (HNSCC) with different HPV16 DNA and RNA (E6*I) status from 290 consecutively recruited patients by gene expression profiling and targeted sequencing of 50 genes. We show that tumors with transcriptionally inactive HPV16 (DNA1 RNA-) are similar to HPV-negative (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
195
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(211 citation statements)
references
References 44 publications
4
195
0
12
Order By: Relevance
“…In addition, there was an association between higher Ki-67 expression and metastases in SACC patients. In HNSCC, HPV-negative tumors appear to be enriched for EGFR and TP53 mutations (25). Herein, there were no correlations of HPV status with p53, EGFR and Ki-67 expression in SACC.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, there was an association between higher Ki-67 expression and metastases in SACC patients. In HNSCC, HPV-negative tumors appear to be enriched for EGFR and TP53 mutations (25). Herein, there were no correlations of HPV status with p53, EGFR and Ki-67 expression in SACC.…”
Section: Discussionmentioning
confidence: 67%
“…In HNSCC, HPV-positive tumors are characterized by certain clinical and pathological characteristics, the expression of certain cell cycle proteins and genetic changes that are different from HPV-negative HNSCC (24,25). TP53 mutations are by far the most common and present in ~70% of HPV-negative HNSCC patients, but rare in HPV-related HNSCC as p53 is targeted by E6 protein (26).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression data (mRNA-seq) and clinical data of 270 head and neck squamous cell carcinomas were obtained from gene expression omnibus (GEO) (http:// www.ncbi.nlm.nih.gov/geo/, accession number:GSE65858) [18]. Clinical data included survival data, gender, age, TNM stage, primary site and HPV status, alcohol, and smoking habit.…”
Section: Gene Expression Data and Clinical Informationmentioning
confidence: 99%
“…Therefore, the objectives of this study were to analyze the expression pattern of ALDH2 and SOD2 genes using available microarray data (GSE65858 and GSE39368) [18] and determine the relationship between the expression level of these two genes and clinical parameters such as alcohol drinking, tobacco smoking, primary site of HNSCC, and human papilloma virus (HPV) state.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have described differences between HPVpositive and HPV-negative OPSCC with regard to RNA expression and differences have mainly been reported in genes involved in immune response, apoptosis, proliferation/ cell cycle and differentiation (74)(75)(76)(77)106). Notably, some studies have, based on transcriptional and HPV data, suggested molecular sub-grouping of HNSCC.…”
Section: Transcriptome Analysis In Opsccmentioning
confidence: 99%